Personality Traits and Sexual Risk Behaviors: The Moderating Role of Religiosity in Maritime Cadets - Ortiz, Dhuff Mattheus Villanueva; De Jose, Elmer Gonzales (Future Science / FSH-PH Publications, 2025)
This research explores whether religiosity moderates the link be-tween Big Five personality traits and cadets' sexual risk behaviors. Overall, 474 respondents participated in the study. This number con-sists of students taking up Marine Transportation and Marine Engi-neering students in a maritime school situated in Metro Manila. They were surveyed using the converted electronic version of the Brief Mul-tidimensional Measure of Religiosity and Spirituality (BMMRS), Big Five Personality Factors - 2 (BFI-2), and the Sexual Risks Behaviors Scale. Based on the results, the study found that agreeableness is neg-atively correlated with sexual risk behavior (r = -.12*, p < .05), sug-gesting a tendency towards lower engagement in risky sexual behav-iors among those with higher levels of agreeableness. Furthermore, this study concluded that religiousness did not moderate the relation-ship between agreeableness and sexual risk behavior. This suggests that, regardless of whether individuals are highly agreeable, their level of religiousness does not seem to alter the impact of agreeableness on sexual risk behavior.